An investigation of Mycobacterium bovis and helminth coinfection in the European badger Meles meles - David J. Kelly; Nicola M. Marples; Rachel L. Byrne; Ursula Fogarty; Kevin Kenny; Henrietta Cameron; Denise Griffin; Celia V. Holland (International Journal for Parasitology: Parasites and Wildlife, 2022)
We investigated the relationship between the presence of helminth parasites in European badgers, and their tuberculosis (TB) status, culled as part of the bovine TB eradication programme in Ireland. Data on the worm burden or faecal egg or larval count was available for all helminth taxa recorded. Lymph node tissue samples were taken from the badgers and tested for TB. We then explored the correlation, in full-grown badgers, between the likelihood of M. bovis infection and both the prevalence and burden of certain helminth species. Specifically, our analyses focused upon the gastrointestinal species, Uncinaria criniformis and Strongyloides spp. We found that male badgers were more likely to have TB than female badgers, and that badgers infected with U. criniformis or Strongyloides spp. were more likely to have TB than badgers without such helminth infections. There was a suggestion that badgers with higher U. criniformis worm burdens were more likely to have TB than those with lesser burdens. Although our sampling protocols did not allow us to determine which infection came first, it strongly suggests that once badgers are infected with either gastrointestinal helminths or TB, they are likely to become coinfected. As Ireland works towards a national TB-free status, it will be important to appreciate the implications of such coinfection.